ChemInform Abstract: Rh(III)‐Catalyzed Tandem C—H Allylation and Oxidative Cyclization of Anilides: A New Entry to Indoles. Issue 4 (28th January 2014) - Cajaraville, Ana; Lopez, Susana; Varela, Jesus A.; Saa, Carlos
Abstract Optimized reaction conditions allow the synthesis of 2‐methylindoles via oxidative cyclization of various acetanilides (I) with allyl carbonate (II).